Antenatal traumatic brain injury secondary to maternal motor vehicle accident - Shamala Nair,; Faizal AH, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Trauma is thought to complicate 1 in 12 pregnancies. The management of trauma during pregnancy requires special consideration because pregnancy alters maternal physiology and the foetus is a potential collateral victim. The approach of these cases in the setting of the Emergency Department should not only be diagnostic for any foetal injuries but also prognostic for any future undue outcome. Antenatal traumatic brain injury is a rare but real complication of maternal blunt force trauma. Our case involves a 22-year-old primigravida who suffered a motor vehicle accident and on initial assessment revealed normal foetal assessment butsubsequently after premature labour revealed a new born with traumatic brain injury. Early ultrasonographic evaluation and observational period with continuous electronic foetal monitoring may improve the detection and emergent treatment in these cases.